Relationship Between Students’ Reading Habit and Their Vocabulary Knowledge - Siti Ithriyah; Novi Nurmalia (Universitas Cokroaminoto Palopo, 2021)
This research aims to find empirical evidence whether there is any relationship between the students’ reading habit and their vocabulary knowledge at the seventh grade students of SMPN 174 Jakarta in 2019/2020 academic year or not. This study use Quantitative method with research design Correlation. The sample used is Random Sampling. On the validity test of the questionnaire, there are 25 questions with 18 questions are valid. On the validity test of vocabulary test, there are 50 questions with 24 questions are valid. For reliability test of questionnaire use K.21 formula, the result of the reliability test of questionnaire is rh = 0.800 > rt = 0.324 so it can be concluded that the questionnaire is reliable. The result of the reliability test of vocabulary test is rh = 0.805 > rt = 0.324 so it can be concluded that the vocabulary test is reliable. In the hypothesis test, t-test was obtained th -0.345 with tt 1.70 at P 0.95 and dk (n-2) = 33 so, H0 is accepted. Because H0 is accepted, Hi is rejected so, there is no significant relationship between two variables.